PRECEDENT PHENOMENA IN MODERN MEDIA TEXTS (ON THE EXAMPLE OF N. V. GOGOL’S WORKS) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-31-40This study is devoted to examining the texts of modern mass communication that contain elements of intertextuality in the form of precedent phenomena. Using the example of N.V. Gogol’s work precedent names, situations, statements were identified, and we analyzed their semantic and grammatical features established in the current media space. The material for the study were precedent units identified by the method of continuous sampling from modern media texts of various directions. As a result of the study, it was proved that journalists give preference to precedent phenomena associated with classical Russian literature with the works of the famous satirist N.V. Gogol. These works as a powerful tool for the formation of metaphorical models and scenarios, with the help of which parallels are drawn between the author's negative images and vices of modernity. Precedent units dating back to the work of N.V. Gogol are identified and described. We determined their semantic and pragmatic features, peculiarities of implementation in the current media space.Key words: precedent phenomena, precedent names, precedent statements, media text, media space, media discourse, Russian literature, N.V. Gogol